The Association Between Time Taken to Report, Lodge, and Start Wage Replacement and Return-to-Work Outcomes. Issue 7 (July 2018) - Cocker, Fiona; Sim, Malcolm R.; Kelsall, Helen; Smith, Peter
Abstract : Objective: The aim of the study was to determine if prolonged times taken to notify, file, adjudicate, and start wage replacement for workers' compensation claims are associated with poorer return-to-work (RTW) outcomes. Methods: Using 71, 607 claims lodged 2007 to 2012, logistic regression determined associations between time to claim filing, adjudication, and payment and (1) socio-demographic/economic, occupational, and injury-related factors; and (2) 52 weeks of wage replacement (WR). Results: Prolonged times for all processing steps were associated with increased odds of reaching 52 weeks of WR. Prolonged times in more than one step increased the odds of a long-term claim. Being female was the only variable consistently associated with each prolonged processing time. Conclusions: The predictive ability of prolonged times in claim lodgement and processing and compensation payments demonstrate that shorter claims management and adjudication times could improve RTW outcomes.